إسهام النشاط الترويحي في تحقيق الأمن النفسي خلال فترة الحجر المنزلي لمواجهة فيروس كورونا المستجد كوفيد 19 - حمية, راشد; تقيق, جمال; براهيمي, قدور (جامعة الوادي - University of Eloued, 2021)
هدفت الدراسة الحالية إلى التعرف على اسهام الأنشطة الترويحية في تحقيق الامن النفسي لدى طلبة المعاهد والجامعات بدولة الجزائر استخدم الباحث الاستبيان الذي شمل17 فقرة موجهة لطلبة معاهد وجامعات من مختلف انحاء الوطن. وبلغت عينة الدراسة 30 طالبا ، استخدم الباحث في هذه الدراسة المنهج الوصفي ، وذلك لملائمته لطبيعة البحث و أظهرت النتائج إلى ان للأنشطة الترويحية دور إيجابي في تحسين السلوك الإنساني ،كما تلعب هده الأخيرة دور إيجابي في التغلب على المواقف السلبية وتساهم في التغلب على الضغط وتخفف من حدة القلق والإحباط وتعتبر من الأساليب الفعالة في التخفيف من التوتر النفسي والتحكم في الانفعالات وتعزيز الثقة بالنفس وتحقيق الأمن النفسي . وأوصت الدراسة الى إدراك أهميـة الأنشطة الترويحية والاهتمام الى تغيير اتجاهات الافراد والاسر نحو ممارسة الأنشطة الترويحية مما يساهم في التقليل من الضغوط وضرورة توفير فنوات اتصال للمتضررين نفسيا تخاطب مشكلاتهم وتقدم لهم المعلومات الأساسية . This study aimed to identify the contribution of recreational activities in achieving the psychological security for students of institutes and universities in Algeria. The researcher used a questionnaire that includes 17 paragraphs addressed to students of institutes and universities across the country . The study sample reached 30 students. In this study, the researcher used the descriptive approach due to its convenience to the nature of the research. The results showed that recreational activities had a positive role in improving human behavior. The latter also plays a positive role in overcoming negative attitudes and contributes to overcoming stress and relieves anxiety and frustration and is considered as an effective method for controlling emotions and reinforcing self-confidence and achieving psychological security. The study recommended to understand the importance of recreational activities and giving attention to changing the attitudes of the individuals and families towards practising recreational activities which contribute to reducing stress and the necessity to provide communication channels to people who are psychologically affected and address their problems and provide them with essential information
The contribution of the recreational activity to achieving the psychological security during the home quarantine period to confront Corona virus Covid19
مقال
Keywords: النشاط الترويحي ، الأمن النفسي ، الحجر المنزلي; recreational activity, psychological security, home quarantine